2020
DOI: 10.1136/archdischild-2020-319388
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of vascular ring arch anomalies influences prognosis and management

Abstract: ObjectiveThis study aimed to explore the anatomical features of aortic arch anomalies associated with vascular rings, hoping to identify those which may increase the risk of symptomatic presentation and surgical intervention.MethodsThis was a retrospective observational study at a single cardiac unit. Individuals diagnosed with an aortic arch anomaly, either isolated or non-isolated, between June 2014 and September 2018 were included. The morphology of the aortic arch was established via analysis of postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The reason for this variance may relate to caseload, for example the study by Young et al 12 reported only 10 cases of isolated RAA‐LD. Whereas other postnatal studies which were undertaken in a pediatric cardiology center 13 and in specialist tracheal unit 14 note similar rates of symptoms as described in this current study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The reason for this variance may relate to caseload, for example the study by Young et al 12 reported only 10 cases of isolated RAA‐LD. Whereas other postnatal studies which were undertaken in a pediatric cardiology center 13 and in specialist tracheal unit 14 note similar rates of symptoms as described in this current study.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas other postnatal studies which were undertaken in a pediatric cardiology center 13 and in specialist tracheal unit 14 note similar rates of symptoms as described in this current study.…”
Section: Comparison To Published Literaturesupporting
confidence: 81%
“…This routinely acquired, additional view of the upper mediastinum has also led to an increase in the detection of right and double aortic arches (RAA/DAA) prenatally. [2][3][4] These anomalies can be associated with chromosomal and genetic syndromes and extracardiac anomalies. A DAA and the subtype of a RAA with left ductal ligament encircle the trachea and oesophagus which can lead to symptoms/signs of tracheoesophageal compression, 5 but there are no population-based studies to help understand how frequently this develops and how expectant families should be counselled or managed after birth.…”
mentioning
confidence: 99%
“…The challenge for management of vascular rings lies in those that are isolated without other forms of congenital heart disease. It has been shown that children with a DAA tend to present earlier with symptoms/signs of trache‐oesophageal compression and are more likely to be associated with residual respiratory post‐operative morbidity compared to RAA 2,4‐13 . with some surgical centres advocating universal early surgery 13‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that children with a DAA tend to present earlier with symptoms/signs of tracheoesophageal compression and are more likely to be associated with residual respiratory post-operative morbidity compared to RAA. 2,[4][5][6][7][8][9][10][11][12][13] with some surgical centres advocating universal early surgery. [13][14][15][16] Accurate prenatal diagnosis of vascular rings assists with perinatal management by facilitating parental education such that possible clinical features can be identified early, leading to timely assessment and treatment.…”
Section: Introductionmentioning
confidence: 99%